Which Dimension of Sustainability Matter for Visitors? An eWOM Analysis of Iceland Attractions - D'Acunto David; Lonardi Serena; Confente Ilenia; Raggiotto Francesco (country:TUR, 2024)
Sustainable tourism is now a widely used paradigm in both tourism research and tourism industry, aiming at balancing the economic, environmental, and socio-cultural aspects of tourism development (Mihalic, 2020). However, usually the environmental dimension is the most adopted from the supply side and is the most well recognized by visitors (e.g. Confente & Scarpi, 2021). The socio-cultural dimension is rapidly assuming momentum as well, particularly when it comes to considering destinations struggling with overtourism (Helgadóttir et al., 2019; Mihalic, 2020). In this vein, sustainability research in tourism has been increasingly focused on social issues, mainly exploring the perspective of residents (e.g. Scarpi et al., 2022), host communities (Zhang et al., 2017) or small tourism enterprises (Zhang & Zhang, 2018); notably, the tourist perspective has been neglected in extant literature on the social dimension (Aydın & Alvarez, 2020). Hence, despite a few exceptions encompassing the three dimensions of sustainability for tourism, there is a need for more research including the socio-cultural dimension together with the well explored environmental one, as perceived by tourists. Tourist social responsibility awareness is defined as the responsibilities of tourists in protecting and improving the socio-cultural interests of a visited destination (Luo et al., 2020; Agapito et al., 2023). An example of socially responsible tourists includes the following review snippet: The guide was a true expert and Island native. I loved going to the new Viking exhibit and hearing about the traditions of this wonderful community! My whole family enjoyed the tour. Tourists can significantly contribute in such direction by behaving socially and environmentally responsibly, thus being actively involved in the multidimensional sustainability of tourism destinations (Ferrari et al., 2021). In addition, tourists’ perceptions of the social and environmental sustainability of the destination are fundamental to loyalty and ...